Larvicide potential of genus Croton L. (Euphorbiaceae) in biological control of Aedes aegypti L. (Diptera: Culicidae) - Vitor Emanuel Sousa da Silva; André Ricardo Ferreira da Silva Rocha; Victor Mateus Pinheiro Fernandes; Hayla Nunes da Conceição; Eliana Campelo Lago (Acta Scientiarum. Biological Sciences, 2020)
The reemerging diseases caused by Aedes aegypti are one of the main public health problems in the world. The control of mosquitoes using larvicidal compounds from products of plant origin is an excellent alternative. This study aims to evaluate the larvicidal potential of fractions in hexane, chloroform, ethyl acetate and hydromethanol from the ethanolic leaf extract of two species of the genus Croton L. (Euphorbiaceae) against larval forms of A. aegypti, as an alternative tool to control this vector. Dry leaves of Croton betaceus Baill. and Croton lundianus (Didr.) Müll. Arg. were used for biological tests. The compounds were extracted with ethanol (99.8%). The ethanolic extracts of the leaves were suspended in a methanol / water solution and were successively subjected to the liquid-liquid division process with solvents of different polarities: hexane, chloroform and ethyl acetate, giving rise to the four fractions. Larvicidal tests were performed with the ethanol extract and fractions resulting from the partition. In the study, the crude extract and the fractions showed larvicidal potential, being hexane fraction the one with greatest activity. Mortality in C. betaceus fractions was up to 40%. Croton lundianus presented mortality of up to 93.33% of the larvae submitted to the test. Data analysis showed larvicidal activity in the crude extract and fractions. The hexane fraction was more effective, especially in C. lundianus.